Achieving drinking water compliance levels for metaldehyde with an acclimated sand bioreactor. (1st October 2020) - Rolph, Catherine A.; Jefferson, Bruce; Brookes, Adam; Hassard, Francis; Villa, Raffaella
Abstract: Metaldehyde removal was delivered to below the 0.1 μg L −1 regulatory concentration in a laboratory scale continuous upflow fluidised sand bioreactor that had undergone acclimation through selective enrichment for metaldehyde degradation. This is the first reported case of successful continuous flow biological treatment of metaldehyde from real drinking water sources treating environmentally realistic metaldehyde concentrations. The impact of the acclimation process was impermanent, with the duration of effective treatment directly related to the elevated concentration of metaldehyde used during the enrichment process. The efficacy of the approach was demonstrated in continuous flow columns at both laboratory and pilot scale enabling degradation rates of between 0.1 and 0.2 mg L −1 h −1 . Future work needs to focus on optimisation of the sand bioreactor and the acclimation process to ensure viability and feasibility of the approach at full scale. Graphical abstract: Image 1 Highlights: 86% metaldehyde removal rate increase after acclimation in laboratory sand bioreactors. Acclimated laboratory sand bioreactor achieved compliance for more than 20 days. Laboratory and pilot scale degradation rates ranged between 0.1 and 0.3 mg L −1 h −1 .